From Autotransplantation to Allotransplantation: A Perspective on the Future of Reconstructive Microsurgery - Levin, L. Scott (Journal of Reconstructive Microsurgery, 2018)
It has been half a century since Susumu Tamai reported on the first thumb replantation. The evolution of reconstructive microsurgery has continually added new applications of the operating microscope for reconstructive surgery and has had profound impact on countless patients. From the time of Harold Gillies until today, the reconstructive ladder has evolved to a reconstructive elevator with the “penthouse” floor being represented by vascularized composite allotransplantation.
Keywords: allotransplantation; VCA; microvascular